Rationalities, Practices, and Resistance in Post-Welfarism. A Comment on Kevin Stenson - Fabian Kessl; Nadia Kutscher (Social Work & Society, 2008)
According to Stenson, the former welfare arrangements are in a process of a fundamental re-ordering. Or as this SW&S-Special Issue claims: the spatial scales of the welfare states are under siege. In this analysis, Stenson affirms the prevalent description of a fundamental shift of former welfare arrangements since the last third of the 20th century (see for welfare policy research, research on human services and social work: Castel 2003; Clarke 2004; Gilbert 2004; Lessenich 2008/forthcoming; Marston/McDonald 2006; Webb 2006). Stenson is interested in one specific aspect of "this shift" in his paper that can be subsumed under the concept of sovereignty. Accordingly, Stenson asks, "how is social order maintained, and how are links maintained between the nation state and populations within its borders (...)?" (3). In terms of the "De- and Re-Territorialization of the Social", Stenson's introductory assumption might be reformulated in the following terms of critical geography: Do we live in "new state spaces" (Brenner 2004) - even though Stenson identifies his analysis as taking "non Marxist forms" while critical geography is largely based on an neo-marxist approach: the regulation theory (6).